(untitled) (Global Journal of Human-Social Science, 2021)
The COVID-19 pandemic not only leads to more mental health problems because of its stressful nature, but it also increases the challenges of providing services for people with mental health needs in the community. This paper discusses the limitations of conventional mental health services and the potential use of information and communication technology (ICT) to increase service accessibility in the context of Hong Kong. We review some of the local studies and services and explain why ICT-enhanced services should play a more important role in the local service system, especially when there is a lack of resources and a need for social (physical) distancing. Some future development directions have been highlighted. We argue that it is necessary to further discuss the use of ICT in mental health services and develop more evidence-based web-based resources that can be incorporated into the local service system.